Navigating peace: Al-Qaradawi's critique of Arab-Israeli relations in the Trump era - Ainul Asyraf Lokman,; Mohd Roslan Mohd Nor, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The signing of the Abraham Accords by many Arab nations revived the issue of normalizing relations with Israel. This agreement has prompted an array of comments from Islamic scholars, one of which comes from Sheikh Dr. Yusuf al-Qaradawi. This paper will examine al-Qaradawi's perspective on the issue of normalising Arab-Israeli relations, focusing on the peace efforts led by the United States (US) under the Trump administration. The analysis was done using the text analysis method. It was based on his fatwas, publications, lectures, and works on his official website, as well as his posts on social media. As a consequence of this agreement, al-Qaradawi' is vehemently opposed to a full normalisation of ties, such as what occurred during the Trump administration, and believes that recognising the unlawful state of Israel is a betrayal of Allah, His Messenger, and the Palestinian people. As long as the Zionists continue to oppress the Palestinian people and unlawfully occupy Palestinian territory, he opposes all efforts to make peace with Israel. Given the contemporary milieu in Muslim societies, where tolerance and open recognition of Israel are on the rise, al-Qaradawi's viewpoint can help Muslims approach the topic of normalising relations with a critical mindset.